VARIABILITY OF CERTAIN MORPHO-FARM CHARACTERS IN NEW RIDGES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this state, the results of the research, carried out in the conditions of medium-salt soil, where the vegetation period of the newly created line with the economic parameters of the plant is 112.2 to 115.2 days, and it is fast-growing compared to the standard variety S-6524. The largest mass of cotton in the box is 6.9 g in the T-1006 line, the smallest is 5.8 g in the T-1050 line, which corresponds to the standard type, the rest of the lines are in intermediate positions. Po masse 1000 zeren, standard type with long fiber and output fiber.